2022
DOI: 10.1016/j.jcmgh.2021.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplakin Maintains Transcellular Keratin Scaffolding and Protects From Intestinal Injury

Abstract: Analysis of intestine-specific mice lacking desmoplakin or both desmoplakin/desmoglein 2 show that these proteins are dispensable under basal conditions. However, desmoplakin is essential for cell adhesion, mechanical resilience, and proper keratin network organization, and protects from intestinal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…DSG2 is associated with the armadillo proteins plakophilin (PKP) and the plakin member desmoplakin (DSP), which mediates attachment to the keratin filament network [30]. DSP is necessary for desmosomal integrity and is essential for cell adhesion [31]. To investigate the effect on the subcellular localization of DSG2‐WT and DSG2‐T730D, we isolated the soluble and insoluble protein pools (supplementary material, Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
“…DSG2 is associated with the armadillo proteins plakophilin (PKP) and the plakin member desmoplakin (DSP), which mediates attachment to the keratin filament network [30]. DSP is necessary for desmosomal integrity and is essential for cell adhesion [31]. To investigate the effect on the subcellular localization of DSG2‐WT and DSG2‐T730D, we isolated the soluble and insoluble protein pools (supplementary material, Figure S3B).…”
Section: Resultsmentioning
confidence: 99%
“…66 The plakin family member DP mediates the adhesion of desmosomes and keratins, and loss of DP leads to impaired keratin attachment to desmosomes and altered desmosomal protein levels. 67 Previous research has indicated that only Dsg2 and Dsc2 are expressed in intestinal epitheliums. 68 A Dsg2 antibody targeting the extracellular domain can specifically block hemophilic Dsg2 interactions.…”
Section: The Apical Junctional Complex In the Paracellular Pathways R...mentioning
confidence: 99%
“…Finally, alterations in desmosome ultrastructure have been detected in patients suffering from inflammatory bowel disease (77,78). Because animal models deficient for Dsg2, Dsc2, and Dp have been shown to have intestinal epithelial barrier defects and disturbed wound healing and are prone to colitis (79)(80)(81)(82), several lines of evidence indicate that disturbed desmosomal adhesion contributes to the pathogenesis of inflammatory bowel diseases (83). In this respect, a new function of desmosomes has been elucidated as they control tight junction structure and function (84,85).…”
Section: Other Desmosome-related Diseasesmentioning
confidence: 99%